(x+3)/(x - 1) = (2x+3)/(2x - 2)

DariaRain7 DariaRain7    1   31.08.2021 13:58    0

Ответы
alextv76 alextv76  31.08.2021 14:00

нет решений

Пошаговое объяснение:

\frac{x+3}{x-1} = \frac{2x+3}{2x-2}. ОДЗ: x\neq 1

\frac{x+3}{x-1}=\frac{2x+3}{2(x-1)}

2(x+3)=2x+3

2x+6=2x+3

6=3, противоречие, значит уравнение не имеет решений.

ПОКАЗАТЬ ОТВЕТЫ
аолесдвда аолесдвда  31.08.2021 14:00

(х+3)(х-1)=(2х+3)(2х-2)

х²+3х-х-3=4х²+6х-4х-6

х²+2х-3-4х²-2х+6=0

-3х²+3=0

-3х²=-3

х²=1

х1=-1 х2=1

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика